Thermodynamic modelling of liquid-liquid extraction of naphthenic acid from dodecane using imidazolium based phenolate ionic liquids - Shah, S.N. (Elsevier B.V., 2016)
In this work, N-alkyl imidazolium based ionic liquids with phenolate anions have been used for the separation of naphthenic acid from model oil. The liquid-liquid equilibrium (LLE) data for the ternary mixture of CnmimPhe, dodecane and naphthenic acid were experimentally obtained at a constant temperature of 303.15 K and atmospheric pressure. The effect of chain length on the extraction capability was observed by calculating the distribution coefficient. The experimental tie line data was correlated using the non-random two liquid model (NRTL) and Universal Quasi Chemical (UNIQUAC) model and new interaction parameters for the ternary systems are reported. The experimental data provides a good correlation with the modelling data and a very low root mean square deviation (RMSD) value was observed for all the systems. Â© 2016 Elsevier B.V. All rights reserved.